A rare case of discrete aortic coarctation in Williams-Beuren syndrome. Diagnostic and therapeutic considerations - Savina Mannarino; Eitan Keizman; Michele Pasotti; Alessia Claudia Codazzi; Elisabetta De Sando; Alessandro Giamberti (PAGEPress Publications, 2015)
Williams-Beuren syndrome (WBS) is a genetic disorder caused by elastin gene deletions, and is characterized by cardiovascular malformations, primarily including supravalvular aortic stenosis and peripheral pulmonary stenosis. We report a case of a neonate who developed severe discrete aortic coarctation, underwent multiple surgical interventions, and was subsequently diagnosed with WBS. Severe discrete aortic coarctation is a rare event in WBS newborns. An abnormally thick aortic wall is present in these patients and is the basis of the failure of the classical approach towards coarctation repair, which consists of end-to-end anastomosis as first surgical choice. Our case, and a very few similar previously documented cases, have all demonstrated recoarctation, which only aortic patch implantation was able to successfully repair. In light of this, we would also like to underline the importance of early WBS diagnosis. Therefore, even in mild syndromic phenotype such as low birth weight or facial dysmorphism that raise the suspicion of a genetic syndrome, it is advisable to perform fluorescent in situ hybridization analysis rather than merely karyotypic one.